A selective metasurface absorber with an amorphous carbon interlayer for solar thermal applications. (August 2016) - Wan, Chenglong; Ho, Yinglung; Nunez-Sanchez, S.; Chen, Lifeng; Lopez-Garcia, M.; Pugh, J.; Zhu, Bofeng; Selvaraj, P.; Mallick, T.; Senthilarasu, S.; Cryan, M.J.
Abstract: This paper presents fabrication, measurement and modelling results for a metal-dielectric-metal metasurface absorber for solar thermal applications. The structure uses amorphous carbon as an inter-layer between thin gold films with the upper film patterned with a 2D periodic array using focused ion beam etching. The pattern has been optimised to give high absorptance from 400 to 1200 nm and low absorptance above this wavelength range to minimise thermal radiation and hence obtain higher temperature performance. Wide angle absorptance results are shown and detailed modelling of a realistic nanostructured upper layer results in excellent agreement between measured and modelled results. The use of gold in this paper is a first step towards a high temperature metasurface where gold can be replaced by other refractory metals such as tungsten or chrome. Graphical abstract: SEM view of a MDM structure. Inset image at higher magnification showing rounded nature of the upper patterned layer. Highlights: First example of a tri-layer metasurface absorber using a carbon interlayer. Very good solar selective performance with potential for high temperature operation. Potential for use within emerging field of diamond thermionic energy converters.